Legal Regulations on Road Traffic Accidents for Motorized Vehicle Owners in Indonesia - Rivan Achmad Purwantono; Gunarto Gunarto; Anis Mashdurohatun; Bambang Tri Bawono (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
Regulations pertaining to the liability of motorized vehicle owners in Indonesia, as stipulated by Law Number 34 of 1964 concerning Traffic Accident Funds and Government Regulation Number 18 of 1965 regarding the Implementation Provisions of Road Traffic Accident Funds, have yet to be implemented since enactment. This is due to the lack of justice for motorized vehicle owners or operators whose vehicles are involved in accidents, but are not under their immediate control. The prevailing regulations do not adequately differentiate between individual and collective liability for traffic accidents. This study aimed to analyze the weaknesses inherent in the existing regulations, particularly in regards to the liability of motorized vehicle owners for accidents, which have not been handled with due fairness. The research paradigm seeks to examine the existing state (das sein) and the ideal state (das sollen) related to the legal liability of motorized vehicle owners.